2002
DOI: 10.1159/000066289
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Localization of Nerves in the Uterosacral Ligament: Determination of the Optimal Site for Uterosacral Nerve Ablation

Abstract: We select surgical treatment for cases for which severe dysmenorrhea persists following medical treatment. Many reports have described the use of neurectomies by cutting off pain conducting nerve pathways using laparoscopic surgery. Laparoscopic uterosacral nerve ablation (LUNA) has been associated with a high success rate for pain control, but there are few reports of anatomical studies in the uterosacral ligament. Using an immunohistochemical method, we examined the number and types of nerve fiber bundles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…However, in two specimens (18%) they emerged from S1 and climbed medially through the IHP. So far, a single mention could be found of the existence of a pelvic sacral nerve emerging from the ventral branches of S1-S4 running inside the uterosacral ligament (Fujii et al, 2002). It has yet to be established on a larger scale whether S1 generally gives rise to a pelvic sacral nerve.…”
Section: Discussionmentioning
confidence: 99%
“…However, in two specimens (18%) they emerged from S1 and climbed medially through the IHP. So far, a single mention could be found of the existence of a pelvic sacral nerve emerging from the ventral branches of S1-S4 running inside the uterosacral ligament (Fujii et al, 2002). It has yet to be established on a larger scale whether S1 generally gives rise to a pelvic sacral nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Recent anatomical studies by Fujii et al showed that the majority of uterosacral nerve fiber bundles were found at a distance of 6.5-33 mm and at a depth of 3-5 mm distal to the site of attachment of the uterosacral ligaments to the cervix. (9,10) ( Fig. 1).…”
Section: Laparoscopic Uterine Nerve Ablation (Luna) Proceduresmentioning
confidence: 99%
“…It has been suggested that division of the uterosacral ligaments approximately 1.5 cm distal to the cervix should interrupt many sensory nerve fibers of the cervix and uterine corpus, and Doyle suggested that this was possible even through the vaginal route [5]. However, anatomical studies showed that the majority of uterosacral nerve fibers were found at a distance of 6.5-33 mm and at a depth of 3-5 mm distal to the attachment site of the uterosacral ligaments to the cervix [26]. There are widespread variations in the technique performed, including the route of surgery, the site of nerve ablation, and the method used for nerve ablation such as laser, electrodiathermy, scissors cutting, or harmonic scalpel [27].…”
Section: Uterosacral Nerve Ablationmentioning
confidence: 99%